Flux growth of superconducting La2CuO4 single crystals - Chen, C; Smith, D; Gay, P; Ryan, J (2000)
We report here the first observation of superconductivity in lanthanum cuprate crystals grown in an ambient atmosphere. The best result achieved so far is: (1) superconducting transition temperature T-c = 32 K with DeltaT(c) similar to3 K by ac susceptibility measurement, and (2) T-c (on set) = 36 K and T-c (zero resistance) = 26 K by resistivity measurements. The solubility curve of La2CuO4 in molten CuO has been established, and large single crystals with size up to 16 x 15 x 0.1 mm(3) have been obtained. The morphology of the superconducting crystals (thin plate) is remarkably different from that of insulating crystals (pyramid), which suggests a layer growth mechanism. The mechanism produces an enlarged unit cell which permits O2- intercalation. This "soft" oxygenation has marked influence on the superconducting properties.